PEMANFAATAN STROKE EARLY DETECTION CARD DALAM MENDETEKSI RISIKO STROKE PADA PEREMPUAN DI WILAYAH KERJA PUSKESMAS LEMPAKE KOTA SAMARINDA - Khumaidi, Khumaidi; Bahtiar, Bahtiar; Syahrun, Syahrun; Muda, Iskandar (Jurnal Pengabdiaan Masyarakat Kasih (JPMK), 2024)
Introduction: Stroke can be prevented early by identifying stroke risk factors. One of the efforts made to detect early is by screening for stroke risk using the Risk Stroke Scorecard which has been established by the National Stroke Association. It is hoped that early detection can help the public in knowing their health status, especially the risk of stroke. Objective: To detect early risk of stroke in women in the Lempake Community Health Center work area, Samarinda City. Method: This activity will be carried out in 2 sessions, namely the first session is for early detection of stroke and then continued with education regarding stroke risk prevention. Results and Conclusions: Most of the community service participants were aged between 19-44 years and had the status of housewives. The results of stroke risk detection showed that 18 participants (60%) were at moderate risk of stroke. Continuous detection and education need to be carried out to prevent stroke.